Security Risk Management in the Electronic Banking Environment: Some Evidence for Banking Systems - Algamdi, Abdelmageed (Milev Journal of Research and Studies, 2020)
The banking industry has witnessed a significant growth in the use of the Internet, and in the procurement of goods and services and electronic data exchange, which requires a secure Internet to achieve a high level of confidence with institutional customers, so banking institutions realized the importance of security and confidentiality in electronic banking operations.The research aims to answer the following question: How to reduce the security risks in the e-banking environment?. In order to achieve the objective of the research, a descriptive analytical approach was adopted and specialized research was used in the field of e-banking risk management, leading to findings and recommendations.